What makes older people want to use mobile devices? - Abd Malik, Sofianiza; Azuddin, Muna; Abdullah, Lili Marziana (Springer Link, 2017)
The use of mobile devices have huge potential to assist mobile users to perform everyday tasks. However, there is small percentage of older people are using mobile devices. This shown that, there is several factors that influenced the small group of older people to adopt the technology. In addition, there have been limited studies which investigate factors that influenced older people to adopt mobile devices. This study aims to understand the cause in which have encourage older people to adopt such technology. Qualitative methods including interview and focus groups were conducted among twenty one older people aged 55 and above. The results indicated that, there were five factors that influence older people to use mobile devices. The factors were mobile device design, functions, social inspiration, economical and others.